SOCIAL MEDIA INFLUENCE ON NIGERIA GENERAL ELECTIONS WITH EMPHASIS ON ENUGU STATE 2023 GOVERNORSHIP ELECTION - Eze, Ngozi Linda; Eze, Hyacinth O.; Obasi, Ferdinand; Onwo, Desmond O. (African Journal of Social and Behavioural Sciences, 2025)
This study aims to investigate the role of social media in Nigeria elections with specific reflection from the 2023 Enugu State Governorship election. The study’s specific objectives include finding out the roles social media played in Nigerian political awareness and participation in the 2023 governorship elections and identifying the depth and frequency of social media coverage on the success of curtailing election rigging and fraud. The study adopted a survey method coupled with social media data gathered from the Nigeria general elections. These data were analysed, and two hypotheses were tested using Chi-Square and Simple Regression Analysis in SPSS version 21. The major findings revealed that social media played a significant role in Nigerian political awareness and participation in the 2023 governorship elections. The coverage of Nigeria’s election through social media curtails election rigging and fraud. In line with the findings, it was recommended that the Electoral Act should be reviewed to provide specific guidelines on the use of social media in Nigeria’s future elections; the use of Electronic Card readers must be perfected to avoid technical hitches as experienced during the last elections; the Independent Nigeria Electoral Commission (INEC) should establish a social media tracking centre to monitor, collate, and interpret trends and reports during elections; and that the INEC, civil society organizations, and security agencies in the Country should establish modalities to systematically verify information reported by citizen observers through social media.